Loading in 5 sec....

Revision Quadratic EquationPowerPoint Presentation

Revision Quadratic Equation

- 114 Views
- Uploaded on
- Presentation posted in: General

Revision Quadratic Equation

Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.

- - - - - - - - - - - - - - - - - - - - - - - - - - E N D - - - - - - - - - - - - - - - - - - - - - - - - - -

Revision Quadratic Equation

Solving Quadratic Equation by Complete the Square Method.

By I Porter

Factoring to solve quadratic equations is generally quite fast and easy, but many quadratics cannot be solved by factorisation.

For example, the quadratic x2 + 5x - 1 = 0, appears to be simple, but cannot be factorised. For these, we must use the COMPLETE THE SQUARE method or the Quadratic Formula.

The Complete the Square method is based on the following two expansion:

(a + b)2 = a2 + 2ab + b2

(a - b)2 = a2 - 2ab + b2

What is really important, is the relationship between ±2b and b2.

This is an important step in the complete the square method of solving quadratic equations.

This could have been solved faster by factoring the original quadratic equation.

x2 + 8x = 0

x (x + 8) = 0

therefore

x = 0 or x + 8 = 0

x = 0 or x = -8

We obtain the same result, but a lot faster!

For ax2 + 2bx + b2 = 0

2b = (+8)

x2 + 8x = 0

To complete the square we need to add b2 = +16 to both sides.

x2 + 8x+ 16 = 0 + 16

x2 + 8x+ 16 = 16

Factorise LHS, simplify RHS.

(x + 4)2 = 16

Take √ of both sides.

x + 4 = ±4

Solve for x.

x = -4±4

i.e. x = -4 - 4 or x = -4 + 4

x = -8 or x = 0

The solution is x = -8 and x = 0.

Example 3

x2 + 8x + 12 = 0

Rearrange to x2 + bx = c

Rearrange to x2 + bx = c

x2 - 5x - 3 = 0

x2 + 8x = -12

For ax2 + 2bx + b2 = 0

2b = (+8)

x2 - 5x = 3

For ax2 - 2bx + b2 = 0

2b = (-5)

To complete the square we need to add b2 = +16 to both sides.

To complete the square we need to add b2 = +25/4 to both sides.

x2 + 8x+ 16 = -12 + 16

x2 + 8x+ 16 = 4

Factorise LHS, simplify RHS.

Factorise LHS, simplify RHS.

(x + 4)2 = 4

Take √ of both sides.

Take √ of both sides.

x + 4 = ±2

Solve for x.

Solve for x.

x = -4±2

i.e. x = -4 - 2 or x = -4 + 2

x = -6 or x = -2

The solution is x = -8 and x = 0.

The solutions should be written in exact form as above.

a) x2 + 6x = 0

b) x2 - 7x = 0

c) x2 - 10x = -9

d) x2 - 6x + 3 = 0

e) x2 + 9x - 5 = 0

f) x2 - 3x - 7 = 0

For ax2 + 2bx + b2 = 0

2b =

To complete the square we need to add b2 = to both sides.

For ax2 + bx + c = 0, if a ≠1 or 0,

step 1 is to divide every term by ‘a’.

Divide by 3 and rearrange to x2 + bx = c

a)

b)

Divide by 2 and rearrange to x2 + bx = c

For ax2 + 2bx + b2 = 0

2b = (+4)

To complete the square we need to add b2 = +4 to both sides.

You need to take CARE!.

Factorise LHS.

Factorise LHS.

Take √ of both sides.

Solve for x.

Take √ of both sides.

Solve for x.

a) 2x2 - 5x - 4 = 0

b) 3x2 + 3x - 5 = 0

c) 2x2 - 7x + 1 = 0

d) 5x2 + 4x - 2 = 0

e) 3x2 - 10x + 2 = 0